The atypical lymphocyte count: a novel predictive factor for severe thrombocytopenia related to dengue. (11th January 2020) - Abeysuriya, Visula; Choong, Clarice Shi Hui; Thilakawardana, Basuru Uvindu; de Mel, Primesh; Shalindi, Malka; de Mel, Chandima; Chandrasena, Lal; Seneviratne, Suranjith L; Yip, Christina; Yap, Eng-Soo; de Mel, Sanjay
Abstract: Background: Early identification of patients at risk of severe dengue disease (DD) is critical to guide its management. We evaluated whether the atypical lymphocyte count (ALC), generated from the Sysmex automated full blood count analyzer, is predictive of severe thrombocytopenia secondary to Dengue infection. Methods: We prospectively collected data on patients admitted with DD between December 2017 and October 2018. ALC data were extracted from the Sysmex XS500i analyzer from day 1 to day 7 of admission. Clinical data were obtained from patients' medical records. Results: We enrolled 256 patients with DD. A negative correlation between ALC on admission and platelet count on day 5 to day 7 (Spearmen's correlation; day 5:-0.485, day 6:-0.428 and day 7:-0.344) (p=0.001) was observed. Based on receiver operator characteristic curve analysis, we found that an ALC of >0.5x10 3 /L had 90% sensitivity and 70% specificity for severe thrombocytopenia (platelet count <50x10 9 /L) on day 5. The positive and negative predictive values were 74.4 and 91.2%, respectively (power 84.7). Conclusions: We propose that ALC on admission may be a novel negative predictive factor for severe thrombocytopenia on day 5 to day 7 of DD. Further studies are required to validate our findings and evaluate whether ALC is predictive of other complications of DD.